Synthesis of alkyl-gem-dichlorocyclopropanes based on isoamylene fraction - A. I. Musin; Yu. G. Borisova; G. Z. Raskil’dina; R. R. Daminev; R. U. Rabaev; S. S. Zlotskii (Тонкие химические технологии, 2021)
Objectives. The study aims to analyze the dichlorocarbenation of the isoamylene fraction, which is a mixture of 2-methyl-butene-1 and 2-methyl-butene-2, in order to obtain the corresponding alkyl-gem-dichlorocyclopropanes in quantitative yield, and also to determine their structure.Methods. In order to determine the qualitative and quantitative composition of the reaction masses, the following analysis methods were used: gas-liquid chromatography (using the Crystal 2000 hardware complex), mass spectrometry (using a Chromatec-Crystal 5000M device with NIST 2012 database), and nuclear magnetic resonance (NMR) spectroscopy (using a Bruker AM-500 device at operating frequencies of 500 and 125 MHz).Results. Alkyl-gem-dichlorocyclopropanes were synthesized from an isoamylene fraction in the presence of catamine AB as a catalyst. Alternatively, isomeric alkenyl-gem-dichlorocyclopropanes were obtained on the basis of isoprene, and by reduction, the corresponding alkyl-gemdichlorocyclopropanes were synthesized. The synthesized substances were analyzed by gasliquid chromatography, mass spectrometry, and NMR spectroscopy, as previously mentioned above.Conclusions. The results show that the dichlorocyclopropanation of the isoamylene fraction proceeds quantitatively with the formation of a mixture of 2-methyl-2-ethyl-1,1dichlorocyclopropane and 2,3,3-trimethyl-1,1-dichlorocyclopropane. Using isoprene, countersynthesis through successive dichlorocarbenation and hydrogenation was used to synthesize 2-methyl-2-ethyl-1,1-dichlorocyclopropane, one of the products of dichlorocarbenation of the isoamylene fraction.